MiR-18 regulates lipid metabolism of non-alcoholic fatty liver disease via IGF1: MiR-18 regulates lipid metabolism of NAFLD - Yang, Hong; Zhang, Bin; Yu, Chun (Cellular and Molecular Biology, 2024)
We aimed to illustrate the regulatory effect of miR-18 on the onset of non-alcoholic fatty liver disease (NAFLD). MiR-18 level in liver tissues collected from NAFLD patients and mice was detected. In vivo and in vitro influences of miR-18 on biochemical indexes, glucose tolerance and insulin resistance (IR) in NAFLD were determined. H&E staining was conducted to observe hepatic steatosis in NAFLD mice. The downstream target of miR-18 was finally detected by luciferase assay. MiR-18 was upregulated in liver tissues collected from NAFLD patients and mice. Knockdown of miR-18 reduced levels of AST, ALT, TG and TC in NAFLD mice and culture medium of FFA-induced LO2 cells. Meanwhile, knockdown of miR-18 alleviated hepatic steatosis and IR in NAFLD mice. IGF1 was the target of miR-18, and it was negatively regulated by miR-18. MiR-18 is upregulated in NAFLD patients and mice. Knockdown of miR-18 alleviates HFD-induced hepatic steatosis and IR through interacting with IGF1 to regulate to lipid metabolism and insulin signals.